Teoretyczne i komparatystyczne uwagi o trybie zmiany konstytucji i jej preambuły - Wojtczak, Daniel; Bisztyga, Andrzej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The article treats on the theoretical and comparative aspects of the amending of the constitution. The Authors' voice is an contribution to the present discussion on amending the binding Constitution of Republic of Poland. The observations are of the juridical, legally technical character, but the article contains the sociological wefts, too. The analisys of the analogical legal solutions, existing in the selected states creates the comparative background of the considerations. Moreover, the Authors undertake the problem of the relation between the normative character of the constitutional preamble and the mode of its amending or annulation.
Keywords: revision of constitution; preamble; amendment of constitution